The influence of herbicide protection on the yield of annual sunflower (Helianthus annuus L.) in the conditions of Western Forest Steppe - I. Mostoviak; I. Krykunov; A. Shuvar; I. Senyk; H. Sydoruk (Карантин і захист рослин)
Methods. Field, quantitative to determine weediness of crops, mathematical and statistical to assess the reliability of the data obtained.